Development of reference buildings to analyze the potential for energy-efficient refurbishment of buildings - Schwan, Lukas; Hahn, Jakob; Barton, Michael; Anders, Ronja; Schweigler, Christian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The building sector offers the largest potential for a significant reduction of greenhouse gas emissions. Based on own preliminary investigations for the State of Bavaria, a complete renovation of the building envelope of the current residential building stock would result in a reduced demand for final thermal energy for space heating and domestic hot water by about 70 %.
Keywords: building sector; renovation of the building; energy-efficient of buildings; energy optimization; energy policy; DesignBuilder; sektor budowlany; remont budynku; budynek energooszczędny; optymalizacja energii; polityka energetyczna